Funções dos músculos do assoalho pélvico e suas relações com a gravidade da incontinência urinária após prostatectomia radical - Maria Cristina da Cruz (2013)
Introduction: Radical prostatectomy (RP) is the most common type of surgery performed to treat prostate cancer. Urinary incontinence (UI) after RP is one of the most important comorbidities because of its high prevalence and impact on quality of life affecting patients physical activity and social well-being. The pelvic floor muscles (PFM) are one of the most important structures responsible for the continence mechanism. Impairment of the PFM may lead to deficiency of the sphincteric mechanism. Therefore, functions of the PFM might be associated to the severity of the UI after RP. Objectives: to describe the following PFM functions in men with UI after RP: capacity of contraction, coordination, strengh and endurance; to investigate the association among these functional variables; to develop predictive models for UI severity based on these functional and clinical variables; and finally to investigate the association between the severity of UI and quality of life in men who underwent RP. Method: this cross-sectional study investigated 83 men with UI who underwent RP in two public hospitals in Brazil. Clinical evaluation was performed after catheter removal to investigate PFM functions (capacity of contraction, coordination, strengh and endurance); sociodemografic and clinical data were collected from hospital records and questionnaires. The severity of UI was investigated by the 24-hour pad test. Quality of life was investigated by the ICIQ-SF. Descriptive statistics, tests of correlation and differences; univariate and multivariate analyses tested 16 potential predictors of severity of UI; significance level was set at 5%. Results: all 83 participants were incontinent at the time of data collection which underwent between 18 days after RP. The mean of the 24-hour pad test was 341,85g. Regarding the PFM functions, 89,2% of the participants presented capacity of contraction but only 26,5% presented coordination, both measured by inspection. The mean strengh, measured by a perineometer was 101,31 cmH2O and the mean endurance, measured using a cronometer, was 11,7 segundos. From the eight preditive factors selected by the univariate analisys, multivariate analyses identified the following: endurance of the PFM (p = 0,001) and age (p = 0,003) or strengh of the PFM (p=0,014) and age (p=0,001) as predictive of the severity of UI. The mean score of the ICIQ-SF was 12,23 and it was positively associated (r = 0,57; p < 0,001) with the severity of UI. Conclusion: the majority of participants were able to contract the PFM, however few presented coordination of the PFM. Strengh was positively associated with coordination and endurance of the PFM. Age, endurance and strengh were indetified as predictors of the severity of the UI in men after RP. PFM function differ among individuals, and have major impact on the severity of UI. Attention should be paid on specific evaluation and training of those functions during the PFM training in order to provide effective rehabilitation and to avoid desnecessary disconfort and embarrassment. Patients quality of life is affected and needs to be addressed by the health care providers.